2019
DOI: 10.1186/s13705-019-0203-6
|View full text |Cite
|
Sign up to set email alerts
|

Transition governance for energy efficiency - insights from a systematic review of Swedish policy evaluation practices

Abstract: Background: The transition towards a more sustainable energy system is urgent for addressing global environmental and social challenges, and will require transformative changes including improved energy efficiency in the built environment. To reach identified efficiency potentials, various policy instruments have been introduced but their effects are often unclear. In this paper, we argue that the outline of transformative policy strategies will require well-designed evaluations. The objective is to present a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Empirical studies applying the presented framework on new Swedish data (Neij et al, 2021;Sandin et al, 2019) have reconfirmed several previous results. Among these results are the predominance of effectiveness and impact as criteria, the quite limited use of theory, the assessment of the contrafactual development mainly limited to the perceptions of the interviewees, and the rare use of triangulation.…”
Section: The Contribution To Meta-evaluations and Evaluation Designsupporting
confidence: 74%
See 2 more Smart Citations
“…Empirical studies applying the presented framework on new Swedish data (Neij et al, 2021;Sandin et al, 2019) have reconfirmed several previous results. Among these results are the predominance of effectiveness and impact as criteria, the quite limited use of theory, the assessment of the contrafactual development mainly limited to the perceptions of the interviewees, and the rare use of triangulation.…”
Section: The Contribution To Meta-evaluations and Evaluation Designsupporting
confidence: 74%
“…This does not imply that all evaluations should be focused merely on transitions, but that their role should clearly increase. Many studies have confirmed that the perception that evaluations largely focus on incremental impacts and effectiveness can clearly be established empirically (Huitema et al, 2011;Sandin et al, 2019;Schoenefeld, 2018). For an evaluation to have a focus on transitions, it implies that the evaluation should evaluate key mechanisms for transitions, that is, experimentation, visioning, and learning for acceleration; they should also be based on a system and multi-actor perspective.…”
Section: Designing Evaluations That Would Better Enhance Transitionsmentioning
confidence: 97%
See 1 more Smart Citation
“…While this may seem fairly obvious, it does raise further questions regarding whether the purpose, the main users, and the channels used for communication are indeed prepared to support a transition. A previous study of current Swedish evaluation practices implied that there is rarely a stated objective within an evaluation to provide knowledge to support a transition [38], and the focus of evaluations is often geared towards a program level. Therefore, while the purpose and reported uses are still seemingly not yet fully aligned for conducting evaluations with a transformative focus, this study indicates a rather robust and varied approach to disseminating results.…”
Section: Strengthening the Use Of Evaluationsmentioning
confidence: 99%
“…Neij et al [37] propose that such a transformative evaluation approach needs to build on insights drawn from various evaluations to deliberately synthesize a broad, holistic, transformative perspective of how different research initiatives and policy instruments are building momentum towards a sustainability transition together. A framework that accounts for the key aspects to consider when performing such transformative evaluations includes drivers for a transition, such as visioning, experimentation and learning, and accounts for a systems and multi-actor perspective, as well as considering reflexivity and the construction of value judgements [37,38]. How such evaluations can actually be facilitated and integrated into current evaluation commissioning and use practices is, however, largely unknown, particularly in the context of facilitating a transition towards a more efficient energy system and society.…”
Section: Introductionmentioning
confidence: 99%